Peningkatan Aktivitas Belajar melalui Strategi Numbered Head Together Berbantu Media Gambar pada Mata Pelajaran Pendidikan Agama Islam (PAI) - Teguh Yunianto; Jannah Ulfah (MODELING: Jurnal Program Studi PGMI, 2021)
This research was conducted with the aim to increase the learning activities of students through the Numbered Head Together (NHT) strategy assisted with media images on Islamic Religious Education subjects. This type of research is a classroom action research using the design of the classroom action research Kurt Lewin model. This research was conducted during III cycles. Each cycle consists of four stages: action planning, action implementation, observation and reflection. The results showed that the Numbered Head Together (NHT) strategy assisted with media images could increase the learning activities of students. This is evidenced by an increase in student learning activities of each cycle. In the first cycle of 67.66%, the second cycle increased to 74.75%, and in the third cycle increased to 82.52% of the total number of VA grade students at SD Negeri Purwodadi Simpang. So it can be concluded that the Numbered Head Together (NHT) strategy assisted with media images can enhance the learning activities of students.